ANALISIS FAKTOR PENYEBAB PERAMBAHAN KAWASAN TAMAN NASIONAL GUNUNG CIREMAI - Amrizal Yusri; Sambas Basuni; Lilik Budi Prasetyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2012)
ABSTRACTGunung Ciremai National Park (GCNP) is one of the conservation areas that has been facing forest land coverchanges due to uncontrolled activities of people around the area. They have been practicing shifting cultivation system for horticulture that can lead to forestdegradation in GCNP area. The aim of this research was to analyzesocio-economic factors that influence expansion in GCNP. Data on sosio-economic were taken in GCNP for one month in August 2010. Collected attributed data including socio-economic conditions, knowledge and attitude of people. The results of image processing were analyzed qualitatively and quantitatively using the attribute data to determine its impact on land cover changes. Socio-economic factors that influenced expansion of land cultivation into the park areas were rate of income in outside area, knowledge especially on cover function and attitude of people to the existing forest. To anticipate expansion of land cultivation into the forest area, the national park should create alternative beneficial projects in order to improve people income outside national park zone, rehabilitation of zone of national park and supervise the activities to people about national park. Keyword: socio-economic, expansion, national park